Gore Vidal a critical companion - Baker, Susan; Gibson, Curtis S. (Critical companions to popular contemporary writers, 1997)
This is the first full-length study to include Vidal's most recent novels and the first designed to meet the needs of the general reader as well as students of contemporary literature. It includes discussions of Lincoln, Empire, Hollywood, and Live from Golgotha, as well as his earlier novels. Baker and Gibson show that while Vidal's novels are tremendously entertaining, they are also serious examinations of a recurring theme - the decline of the West in general and the decline of the United States in particular. A biographical sketch precedes a general discussion of Vidal's early novels. The discussion of each novel includes sections on plot and character development, thematic issues, narrative style, and an alternative critical approach from which to read the novel. A complete bibliography of Vidal's fiction, as well as selected reviews and criticism, complete the book and will be helpful to students, librarians, and adult book discussion participants.